DEVELOPMENT OF GLOBAL ORGANIC GRAIN MARKET IN THE CONTEXT OF ENERGY EFFICIENCY OF PRODUCTION - Paptsov, Andrey; Avarskii, Nabi; Stavtsev, Alexandr; Fedyushin, Dmitry; Rozanova, Тatiana (Revista Inclusiones, 2020)
The paper explores the economic aspects of the development and operation of the organic grain product subcomplex in the European Union and the USA. The index method is used to provide statistical analysis of the structure of crop areas, yields, gross grain production and market outlook. Specific consideration is given to the production of various types of organic grain, namely, wheat, barley and corn.